Android-connected arm-based voltammetry technique for amperometric sensing system / Wan Muhammad Hilmi Wan Zaidi - Wan Zaidi, Wan Muhammad Hilmi (2017)
Potentiostat is a common device or tool that been used in the nanobiotechnology research. This project addresses the need for a potentiostat that is capable of performing differential pulse voltammetry (DPV) technique on an electrochemical detection in research and development industry. The objective of the project is to design a microcontroller based on measurement instrumentation for an amperometric sensing system to detect hybridization and redox reaction that can happen by using differential pulse voltammetry technique. Furthermore, the device also includes the output interface of the potentiostat by display the output in Androids apps via bluetooth connection. To control the 3-electrode sensor, a potentiostat is required. A specific type of control signal, generated and fed to the potentiostat and data obtained from the potentiostat is further processed using system that has been setup in the microcontroller. The microcontroller acts as both, a control unit to drive the electroanalytical technique Differential Pulse Voltammetry as well as data interpretation of potentiostat electrical output based on signal processing algorithm and transfer it to the Android app via bluetooth module. The data analysis is based on the IV characterization and theory of redox reaction that occurs in ferrocyanide solution.